Establishing a successful perioperative geriatric service in an Australian acute surgical unit. Issue 6 (18th February 2018) - Styan, Lauren; Murphy, Skyle; Fleury, Aisling; McGowan, Brian; Wullschleger, Martin
Abstract : Background: The purpose of this study was to assess the impact of a perioperative geriatric service (PGS) in an acute surgical unit (ASU) on patient and organizational outcomes. Methods: Single centre retrospective cohort study. Inclusion criteria were patients over the age of 65 admitted to the ASU between January and June 2014 (pre‐PGS) and 2015 (post‐PGS). Chart reviews were performed to identify outcomes of interest including in‐hospital morbidity and mortality, length of stay (LOS), 30‐day representation and mortality. Results: Geriatric admissions increased by 32% over the two study periods (154 pre‐PGS and 203 post‐PGS). Surgical intervention increased by 11% ( P = 0.01). Significantly more medical complications (14% versus 33%, P < 0.001) were identified after the implementation of the PGS. Recognition of delirium in the over 80s also increased by 57%. Rate of surgical complications was unchanged over the study (28% pre‐PGS and 34% post‐PGS, P = 0.6). In‐hospital (<1%, P = 0.5) and 30‐day mortality (<1%, P = 0.6) remained low, as did 30‐day representation (10% versus 8%, P = 0.5). A trend towards decreased LOS of 1 day was identified after the implementation of the PGS ( P = 0.07). Conclusion: This study demonstrated successful implementation of a PGS into an ASU. This multi‐disciplinary approach has been effective in maintaining low numbers of surgical complications, in‐hospital mortality, LOS and patient representations despite an increased number of medical complications. This likely reflects more timely recognition and intervention of medically unwell patients with the PGS.